Directed reading lessons and second graders' comprehension strategies, and attitude toward reading informational texts - Vinluan, Tina Roisin B. (College of Education, University of the Philippines Diliman, 2019)
The quasi-experimental research determined the effects of Directed Reading Lessons (DRLs) on the comprehension, use of comprehensive strategies, and attitude toward reading Filipino information texts. A one group pretest-posttest design was administered to 25 second graders from a laboratory school in Quezon City. Research tools included comprehension tests, comprehension strategy assessments, and reading attitude assessments toward Filipino informational texts. Paired t-test results showed that DRLs were effective in teaching reading comprehension. The students performed better in answering text-based as compared to inference questions. Qualitative analysis of the comprehension strategy assessments revealed that DRLs had effects on second graders use of comprehension strategies, however, they have difficulty expressing and writing their ideas in Filipino. The tally of the students answers in the questions showed that the students still performed to read narratives over informational texts. The Wilcoxon Signed Rank Test showed that DRLs did not have a significant effect on the participants attitude toward reading Filipino informational texts. Lastly, Spearman Rhos Correlation using the post-treatment data showed that reading comprehension and reading attitude were positively correlated. Hence, it is recommended that DRLs should be used to scaffold learning about comprehension in the early grades. Further research may examine the use of informational texts in other content areas such as Science, those written in English, and those in narrative forms. Moreover, subsequent research that have similar variables may use checklists, observations, focus group discussions, and interviews as research instruments.